Identification of Source Factors of Carbon Dioxide (CO2) Emissions in Concreting of Reinforced Concrete. (2015) - Hermawan,; Marzuki, Puti F.; Abduh, Muhamad; Driejana, R.
Abstract: Construction is a sector that consumes various materials which comes from many sources. Cement and steel (i.e. rebar) part of material used in construction, are combined forming a material called reinforced concrete. In general, reinforced concrete is closely associated with the structure of the building, both low rise building and high rise building structure. In practice, reinforced concrete usage as structural material becomes a strategic issue in the effort to support green construction, especially with regard to the exhaust gas emissions of carbon dioxide (CO2 ). A carbon dioxide (CO2 ) emission in the use of reinforced concrete is produced by the use of fuel in concreting equipment such as tower cranes and concrete pump. The purpose of this research is to obtain potential factors for the source of carbon dioxide emissions (CO2 ). The research object was carried out on several high rise buildings. The definition of high-rise building in this research is a building with a height of 40 m or higher. The sampling method used in this research is random sampling, while the analysis in this research used a descriptive analysis. The research findings show that there are seven factors that could potentially be a source of carbon dioxide emissions (CO2 ) in the concreting of reinforced concrete at a high rise buildings. These seven factors are scope, time, cost, quality, resources, procurement and material transfer.